Call for research hosts: Capacity building through research stays for low-emission agriculture - CGIAR Initiative on Low-Emission Food Systems (2023)
The Climate, Food and Farming, Global Research Alliance Development Scholarships Programme (CLIFF-GRADS) is a joint initiative of the Global Research Alliance on Agricultural Greenhouse Gases (GRA) and the CGIAR Research Initiative on Low-Emission Food Systems. The CLIFF-GRADS Programme builds capacity in early-career scientists from low- and middle-income countries to conduct applied research in agriculture emission quantification and mitigation.